2023
DOI: 10.21203/rs.3.rs-2915225/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of aperiodic components in distinguishing Alzheimer's disease from frontotemporal dementia

Abstract: Background: Distinguishing Alzheimer's disease (AD) from frontotemporal dementia (FTD) poses a clinical challenge, and to address this, inexpensive and accessible techniques, such as electroencephalography (EEG), are increasingly being employed. However, current studies on electrophysiology have not adequately separated aperiodic activity from spectral analysis and have instead evaluated the combination of periodic oscillatory components and aperiodic components. As the understanding of aperiodic activity has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…If the results in our data and Wang et al (2023) are reliable, then the alpha band is likely a fulcrum balancing the lower-frequency (LFO; delta and theta) power and higher-frequency (HFO; beta and gamma) power. The result shows increased aperiodic exponent in AD patients, which means the slope is steeper, leading to increasing LFO power and decreasing HFO power ( Figure 3C ; Wang et al, 2023 ). In terms of excitation/inhibition (E/I) imbalance, it depicts a hypoexcitability state ( Gao et al, 2017 ), which is not the case in the AD animal model of Palop and Mucke (2016) , which is also contrary to a recent study showing that AD patients have a lower aperiodic gamma frequency exponent and decreased DFA exponent, which suggests a flatter slope (i.e., hyperexcitability state) and an E/I imbalanced state, respectively ( van Nifterick et al, 2023 ).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…If the results in our data and Wang et al (2023) are reliable, then the alpha band is likely a fulcrum balancing the lower-frequency (LFO; delta and theta) power and higher-frequency (HFO; beta and gamma) power. The result shows increased aperiodic exponent in AD patients, which means the slope is steeper, leading to increasing LFO power and decreasing HFO power ( Figure 3C ; Wang et al, 2023 ). In terms of excitation/inhibition (E/I) imbalance, it depicts a hypoexcitability state ( Gao et al, 2017 ), which is not the case in the AD animal model of Palop and Mucke (2016) , which is also contrary to a recent study showing that AD patients have a lower aperiodic gamma frequency exponent and decreased DFA exponent, which suggests a flatter slope (i.e., hyperexcitability state) and an E/I imbalanced state, respectively ( van Nifterick et al, 2023 ).…”
Section: Discussionmentioning
confidence: 62%
“…The changing trend in the center frequency is consistent in the aging and AD process. In contrast, the trend in aperiodic parameters (i.e., offset and exponent) is the opposite in both conditions, decreases across aging ( Donoghue et al, 2020 ; Merkin et al, 2023 ) and increases in AD ( Figure 3E ; Wang et al, 2023 ). If the results in our data and Wang et al (2023) are reliable, then the alpha band is likely a fulcrum balancing the lower-frequency (LFO; delta and theta) power and higher-frequency (HFO; beta and gamma) power.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Similar to classical studies, this study assumed that changes in the neural power spectra reflected the changes in oscillatory activities associated with cognitive impairment. However, recent studies have demonstrated the contribution of aperiodic component as a predictor of cognitive impairment, which found that the aperiodic components differed between AD vs. FTD ( Wang et al, 2023 ) and DLB/PD vs. MCI/control ( Rosenblum et al, 2023 ), while other studies showed no differences in the aperiodic components among healthy controls, patients with MCI, and patients with AD ( Azami et al, 2023 ; Kopčanová et al, 2023 ). In examining the correlations between RPs and NPAs, this study demonstrated that the correlational directions were flipped between low- (from RPd to RPa1) and high-frequency bands (from RPa3 to RPhg), with a border transition at RPa2 ( Figures 1 , 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%